-2-z=4.5

Simple and best practice solution for -2-z=4.5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2-z=4.5 equation:


Simplifying
-2 + -1z = 4.5

Solving
-2 + -1z = 4.5

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + -1z = 4.5 + 2

Combine like terms: -2 + 2 = 0
0 + -1z = 4.5 + 2
-1z = 4.5 + 2

Combine like terms: 4.5 + 2 = 6.5
-1z = 6.5

Divide each side by '-1'.
z = -6.5

Simplifying
z = -6.5

See similar equations:

| (6-x)/(x-2)-(5x-7)/(2-x) | | 6=-8x-2 | | 114-10x=9x+19 | | 752.6-78.85= | | x+1/6=x-1/x | | 6x-5=7x+5 | | 2-5r=4-2r | | 1582/0.4 | | x+2/2x+13 | | (2q+3/3)+(3q-4/6)=q-2/2 | | a^4+9=10a^2 | | 2x*x-5x=0 | | 2q+3/3+3q-4/6=q-2/2 | | -1/4x+31/2=-5/8 | | 4/12=x+2/2x+13 | | 0=8n^2+2n | | .03w-.8(w-0.62)=40 | | 4/12=2x+13 | | -7x-18=-144 | | 2x+62=5x-7 | | 2x+6x=5x+-7 | | 2x+6z=5x-7 | | 3x-1+2x=4 | | -3(k-2)-(-6k-4)=-2 | | 49-6x=21x+19 | | 8n+25=9n | | 5n^3-10n^2+3n-6= | | 13-7x=53-21x | | 6.7a-13.4=2.8a+110.23 | | (2x+3y)+(3x-y+2)=80 | | 112-2x=16x+20 | | 2x+3y=40 |

Equations solver categories